Pseudoaneurysms with Associated Vertebral Artery Dissections: An Analysis of a 310 Patient Cohort. (16th November 2020) - Shlobin, Nathan A; Prasad, Nikil; Mitra, Akash; Azad, Hooman; Cloney, Michael; Hopkins, Benjamin; Dahdaleh, Nader S
Abstract: INTRODUCTION: Vertebral artery dissections (VADs) are a particularly common cause of stroke in young patients. Vertebral artery dissections can result in various secondary effects based on the dissection plane, including pseudoaneurysm if the plane of dissection is between the media and adventitia. METHODS: We conducted a retrospective chart review of patients with vertebral artery dissections who presented to our institution at the time of dissection and had a minimum of 3 month follow-up. We collected data on demographics, comorbidities, event characteristics, treatments, and outcomes in the form of modified Rankin scale (mRS) scores. We also conducted multivariate analysis to identify factors independently associated with mRS at discharge and last follow-up. RESULTS: Of 310 patients with VAD, 301 patients had an identified pseudoaneurysm status, with 54 pseudoaneurysm-associated VADs and 147 VADs not associated with pseudoaneurysm. VAD patients with associated pseudoaneurysms were more likely to be female ( P < . 0041), have bilateral VADs ( P < . 0001), and have fewer vertebral artery segments affected ( P = . 0176). VAD patients with pseudoaneurysms were less likely to have occlusion of the vertebral artery ( P < . 0001). VAD patients with associated pseudoaneurysms were more likely to have a higher mRS at 3 month follow-up ( P = . 044) but not at discharge ( P = . 18) or last follow-up ( P = . 05), while VAD patients with and without pseudoaneurysms were equally likely to have improvement in their mRS at 3 months ( P = . 36) and last follow-up as patients without pseudoaneurysms ( P = . 80). VAD patients with and without pseudoaneurysms were equally likely to have resolution of occlusion ( P = . 40) and stenosis ( P = . 19) on radiographic imaging. Presence of a concomitant fracture independently predicted mRS at discharge, while Charlson Comorbidity Index predicted mRS at last follow-up. CONCLUSION: VADs with concomitant pseudoaneurysms are neither associated with worse functional nor radiographic outcomes. VADs should be the primary focus of treatment in patients with concomitant pseudoaneurysms.